What Is Metropolitan Planning and Governance for? - Galland, Daniel; Harrison, John; Tewdwr-Jones, Mark (Springer, 2020)
This concluding chapter argues for a new role of planning in shaping metropolitan futures and reflects on the value of the book’s thematic-temporal-phronetic (TTP) framework—a meso-level approach to better understand the dynamics of contemporary metropolitan change. We begin by revealing the extent to which institutions, policies, spatial imaginaries and planning are influencing metropolitan development through a synthesis of the key outcomes emanating from the totality of the book contributions. The chapter then returns to the TTP framework to reflect on its tripartite rationale as well as its significance to international comparative research. Set against this context, the chapter then identifies four sets of issues that seem highly relevant to both shape future styles of governance and planning, and provide metropolitan regions with modes of working that could make a difference. We finally conclude with three open propositions relating to thematic, temporal and phronetic priorities for future research targeting the planning and governance of metropolitan regions.
Keywords: Metropolregion; Planungsebene; Zukunftsentwicklung; Regionalforschung; Planungsinstitution; Regionalpolitik; Planungsleitbild; Planungsansatz; Internationaler Vergleich; Mittlere Planungsebene; Institutioneller Wandel